Muslim Baduy: Konversi Agama Adat Leluhur - Abdul Syukur; Omang Komarudin; Gustiana Isya Marjani; Dadang Kahmad (Jurnal Penelitian, 2021)
This study raises the main issue of the religiosity of Muslim Baduy after converting to Islam in Leuwidamar, Lebak-Banten. The discussion aims to reveal the factors and the process of converting to Islam, to discover the religious behavior after converting to Islam and the impact of religious conversion on social and cultural changes of Muslim Baduy. The research is a descriptive-analytic study with an ethnographic method by using participant observation, in-depth interviews and documentation techniques. By using Rambo’s theory on the religious conversion stages and Glock and Stark’s theory on the religiosity, it has resulted a conclusion that the religiosity of Muslim Baduy in Leuwidamar, Lebak Regency, Banten is seen as a dynamic process based on the findings: 1) the conversion of Baduy people to Islam is due to political, theological, psychological, and sociological factors. 2) In one hand, Muslim Baduy leaves some tradition of Baduy particularly the rituals of Sunda Wiwitan and practices their obligation as a Muslim. On the other hand, Muslim Baduy still practices some Baduy tradition which is in line with Islamic shari’a.